Cracks of Presence#1: Plastic solitude (Revista Apotheke, 2025)
This paper presents notes and reflections for the creation of an art installation which has as theoretical inspiration the thought about presence production by Hans Ulrich Gumbrecht (2010). The author suggests epistemological alternatives to the cartesian predominance of the Humanities in the incessant search for interpreting and attributing meaning to the analyzed phenomena and defends that the aesthetic experience will always confront us with the tension between presence and meaning. However, only the presence effects appeal with intensity to the senses. We will also dialogue with Georges Didi-Huberman’s (2010) thought when he refers that every eye carries its wrapping and the challenge is to let a gap open in this wrapping, allowing the gaze to open a gap in what it sees.
Keywords: Art Installation; Video Installation; Presence Production; Media Arts; Look